"Who Wants to Go Repeatedly to the Hospital?" Perceptions and Experiences of Simplified Medical Abortion in Rajasthan, India - Kirti Iyengar; Marie Klingberg Allvin; Sharad D. Iyengar; Kristina Gemzell Danielsson; Birgitta Essén (SAGE Publishing, 2016)
The aim of this study is to explore women's experiences and perceptions of home use of misoprostol and of the self-assessment of the outcome of early medical abortion in a low-resource setting in India. In-depth interviews were conducted with 20 women seeking early medical abortion, who administered misoprostol at home and assessed their own outcome of abortion using a low-sensitivity pregnancy test. With home use of misoprostol, women were able to avoid inconvenience of travel, child care, and housework, and maintain confidentiality. The use of a low-sensitivity pregnancy test alleviated women's anxieties about retained products. Majority said they would prefer medical abortion involving a single visit in future. This study provides nuanced understanding of how women manage a simplified medical abortion in the context of low literacy and limited communication facilities. Service delivery guidelines should be revised to allow women to have medical abortion with fewer visits.